Necesidades de atención en enfermería a la gestante con diagnóstico de mortinato (2021)
Perinatal loss in any week of gestation is a frustrating and devastating experience for any human being, for which a timely and quality nursing intervention is required, from this derives an adequate communication with the family that goes through this process and about all an experience where memorable moments can be rescued to properly conclude an acceptance process.